Political competition and economic performance: Empirical evidence from Pakistan - Ahmed Chaudhry; Ummad Mazhar (Kiel Institute for the World Economy (IfW), 2018)
The influence of politics on economic policy is not fully understood. The challenge to ensure political inclusiveness and economic prosperity remains. Perhaps, one way to attain this objective is by increasing political competition. This paper gathers empirical evidence from Pakistan, a country with a checkered political history characterized by episodes of representative, non-representative, and indirectly elected governments. In recent years, the country has witnessed a gradual strengthening of democratic rule with economic progress. Focusing on nine elections held over 1970 to 2015 the authors measure political competition and estimate its impact on economic performance. Contrary to popular conceptions about Pakistan's economic performance, they find a positive association between lack of political competition and poor economic performance. This finding holds at national as well as subnational levels in Pakistan and withstands a number of robustness tests.
Keywords: H50; H83; D70; 330; Political Competition; Pakistan; Economic Performance; Subnational